Vakthund utan tänder - En studie av de konstitutionella begränsningarna för EU-rättens genomslag i svensk rätt och möjligheterna till konstitutionell kontroll - Bobovac,Emil (2025)
This thesis examines the constitutional limitations governing the domestic effect of EU law in Sweden, with particular emphasis on Chapter 10, Section 6 of the Instrument of Government and the ability of Swedish courts to exercise constitutional review of EU law. While this issue has received little attention Swedish legal discourse, it has been more extensively developed in several other EU Member States. The aim is to analyse how such review may be interpreted and constructed within the Swedish legal framework. The study adopts two complementary perspectives: a domestic constitutional perspective, which explores the constitutional basis for such review by examining the relationship between the legislature and the judiciary; and a pluralist perspective, which situates constitutional review in relation to EU law. In addition, the thesis considers how constitutional review has been applied in the case law of other EU Member States. The analysis demonstrates that Sweden’s constitutional limitations are narrowly defined, vaguely formulated, and, in practice, seldom applied by the courts. This reflects both the judiciary’s traditionally restrained role as a constitutional actor and the legislature’s commitment to preserving political discretion in relation to EU law. By contrast, several other EU Member States have developed clearer and more formalised mechanisms of constitutional review, often with the aim of safeguarding sovereignty, fundamental values, and the protection of fundamental rights. The thesis concludes that Swedish courts have established only a limited practice of constitutional review of EU law’s domestic effects, and that the conditions for expanding such review are generally absent. A more robust constitutional review would entail a significant shift of authority from the political sphere to the judiciary, fundamentally challenging the principle of popular sovereignty in favour of a rule-of-law-oriented model of separation of powers. However, there is potential for an indirect constitutional review through a more active and strategic use of the preliminary reference procedure to facilitate dialogue between Swedish courts and the Court of Justice of the European Union.
Keywords: EU-rätt; konstitutionell rätt